Oocytes With Smooth Endoplasmic Reticulum Aggregates Are Not Associated With Impaired Reproductive Outcomes: A Matched Retrospective Cohort Study - Xu, Jian; Yang, Li; Chen, Zhi-Heng; Yin, Min-Na; Chen, Juan; Sun, Ling (Frontiers in Endocrinology, 2021)
Objective: To investigate whether the reproductive outcomes of oocytes with smooth endoplasmic reticulum aggregates (SERa) are impaired. Methods: A total of 2893 intracytoplasmic sperm injection (ICSI) cycles were performed between January 2010 and December 2019 in our center. In 43 transfer cycles, transferred embryos were totally derived from SERa+ oocytes. Each of the 43 cycles was matched with a separate control subject from SERa- patient of the same age (±1 year), embryo condition, main causes of infertility, type of protocols used for fresh or frozen embryo transfer cycles. The clinical pregnancy, implantation, ectopic pregnancy and live birth rate were compared between the two groups. Results: 43 embryo transfer cycles from SERa- patient were matched to the 43 transferred cycles with pure SERa+ oocytes derived embryos. No significant difference was observed in clinical pregnancy rate (55.81% vs. 65.11%, p=0.5081), implantation rate (47.89% vs. 50.70%, p=0.8667) and live birth rate (48.84% vs. 55.81%, p=0.6659) between the SERa+ oocyte group and the matched group. No congenital birth defects were found in the two groups. Conclusion: Our results suggest that the implantation, clinical pregnancy, live birth and birth defects rate of embryos derived from oocytes with SERa are not impaired. Key words: smooth endoplasmic reticulum aggregates, oocyte, cohort study, implantation rate, clinical pregnancy rate, live birth rate.